Characterizing environmental low flows in terms of magnitude, duration and frequency - Kenner, Scott J., author; Nergui, Soninkhishig, author; Sodnom, Tumurchudur, author; Khurelbaatar, Tsogzolmaa, author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
Increased water demand has led to the need for development of water resources in Mongolia. With the Mongolian government implementation of integrated water resources management approach, assessing environmental flow requirements of major rivers becomes a primary issue. Using Indicators of Hydrological Alteration tools, physical habitat survey at Orkhon-Orkhon gauge site and statistical analysis of annual maximum flows, environmental low flow scenarios have been developed that attempt to reflect more "natural" characteristics of magnitude, frequency and duration. Specifically, minimum seasonal low flows of greater than the 75th percentile flow duration with bankfull flow releases during wet periods that have a duration of 12 to 24 days.
Presented at the Building resilience of Mongolian rangelands: a trans-disciplinary research conference held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Keywords: environmental flow; bankfull flow